1996
DOI: 10.1074/jbc.271.46.29265
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning and Characterization of the Human Interleukin 13 Receptor α Chain

Abstract: Interleukin 13 (IL-13)1 is a T-cell-derived cytokine that exhibits a broad range of activities in the regulation of inflammatory and immune responses. Many of the actions of IL-13 are also exhibited by another T-cell-derived cytokine, IL-4, with which it shares approximately 30% amino acid sequence identity. These shared activities include down-regulation of inflammatory cytokines (1), induction of expression of the IL-1 receptor antagonist (2), induction of surface expression of class II major histocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
176
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(179 citation statements)
references
References 29 publications
2
176
0
1
Order By: Relevance
“…Previous studies have demonstrated that the attachment of radiolabeled IL-13 to the functional heterodimer receptor can be competed by IL-4 as well as IL-13, [30][31][32]49 whereas its attachment to IL-13R 2 is competed by IL-13 but not IL-4. 2,9,10,15,33,36 To confirm that the cytotoxicity of IL-13 cytotoxin was specifically mediated through IL-13R 2 chain delivered by Ad-IL-13R 2 vector, A549 cells were infected with Ad-IL-13R 2 at MOI 10 followed by treatment with IL-13 cytotoxin (10 ng/ml) in the presence of a 50-fold dose of human IL-13 or IL-4.…”
Section: Il-13 But Not Il-4 Competitively Inhibits Cytotoxicity Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that the attachment of radiolabeled IL-13 to the functional heterodimer receptor can be competed by IL-4 as well as IL-13, [30][31][32]49 whereas its attachment to IL-13R 2 is competed by IL-13 but not IL-4. 2,9,10,15,33,36 To confirm that the cytotoxicity of IL-13 cytotoxin was specifically mediated through IL-13R 2 chain delivered by Ad-IL-13R 2 vector, A549 cells were infected with Ad-IL-13R 2 at MOI 10 followed by treatment with IL-13 cytotoxin (10 ng/ml) in the presence of a 50-fold dose of human IL-13 or IL-4.…”
Section: Il-13 But Not Il-4 Competitively Inhibits Cytotoxicity Of mentioning
confidence: 99%
“…24,25 It is critical for tumor immunosurveillance 26,27 and modulates apoptosis or tumor cell growth. 28,29 Two different components of the IL-13 receptor have been identified, which are known as IL-13R 1 chain [30][31][32] and IL-13R 2 chain. 33,34 IL-13R 1 chain alone binds IL-13 with low affinity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overlapping functional and biochemical activities of IL-4 and IL-13 can be explained by the fact that their receptors share the IL-4Ra chain (Lin et al, 1995;Zurawski et al, 1995). Unlike IL-4, the IL-4Ra chain is unable to recognize IL-13 by itself, but when combined with the IL-13Ra chain the complex binds IL-13 with a high a nity (Aman et al, 1996;Hilton et al, 1996).…”
Section: Stat6 and The Il-4 Receptormentioning
confidence: 99%
“…[7][8][9][10][11][12] IL-13 has 2 cognate receptors, IL-13 receptor α1 (IL-13Rα1) and IL-13 receptor α2 (IL-13α2). [13][14][15][16][17][18] IL-13Rα1 binds IL-13 with low affinity by itself, but when paired with IL-4 receptor α, it binds IL-13 with high affinity, forming a signaling IL-13 receptor. 16 IL-13Rα2 binds IL-13 with high affinity and acts as a decoy receptor, as shown by IL-13Rα2 knockout mice.…”
mentioning
confidence: 99%